2015
DOI: 10.1007/s12012-015-9337-8
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Phthalic Acid Induces Increased Blood Pressure, Oxidative Stress, and Markers of Endothelial Dysfunction in Rat Offspring

Abstract: Previous studies have reported the harmful effects of exposure to phthalic acid (PA) on heart. No studies have reported the effects of prenatal PA exposure on the structure or function of heart. The current study aimed to investigate the effects of prenatal PA exposure on the markers of oxidative stress and cardiac structure in rats' offspring. Twenty-four pregnant rats were randomly categorized into three groups of control, exposed to 2.5 and 5 % PA. The morphometric properties of coronary arteries, markers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The mice systolic BP measurements showed a significant increase (22%) after 10 mg/kg/day DEHP exposure, which was consistent with the findings of Lee et al where a 30 mg/kg/day maternal DEHP exposure increased the systolic BP by 20% [ 29 , 32 ]. These results were also proved by the authors through the histopathological analysis, which showed a significant thickening of the interventricular septum and the ventricular wall at the same dosage, which were in accordance with the histopathological results of the Rahmani et al study [ 30 ]. Then, the authors measured the levels of ACE, bradykinin B2 receptor (BK2R), eNOS, bradykinin, Ca 2+ , and NO, all related with blood pressure regulation.…”
Section: Animal Studiessupporting
confidence: 85%
See 2 more Smart Citations
“…The mice systolic BP measurements showed a significant increase (22%) after 10 mg/kg/day DEHP exposure, which was consistent with the findings of Lee et al where a 30 mg/kg/day maternal DEHP exposure increased the systolic BP by 20% [ 29 , 32 ]. These results were also proved by the authors through the histopathological analysis, which showed a significant thickening of the interventricular septum and the ventricular wall at the same dosage, which were in accordance with the histopathological results of the Rahmani et al study [ 30 ]. Then, the authors measured the levels of ACE, bradykinin B2 receptor (BK2R), eNOS, bradykinin, Ca 2+ , and NO, all related with blood pressure regulation.…”
Section: Animal Studiessupporting
confidence: 85%
“…The authors showed a significant increase in the offspring BP associated with the increased phthalic acid exposure due to cardiac hypertrophy and a significant increase in the thickness of the aorta wall and the descending left coronary artery. It was also demonstrated that phthalic acid significantly increased the oxidative stress and decreased the antioxidant capacity of the cardiac tissue, which, in turn, are related to vascular dysfunction [ 30 ]. In 2017, Jaimes et al showed that mice exposed to DEHP suffered alterations in the heart rate and cardiovascular response.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 , 20 Importantly, the majority of studies investigating the effects of gestational phthalate exposures on cardiovascular outcomes have focused only on males. 11 , 12 , 21 Although work from our lab and others demonstrate sexually dimorphic effects of endocrine-disrupting chemicals, including phthalates, in humans and animal models, 6 , 22 - 24 little is known about the sex-specific effects of gestational exposure to phthalates on the heart.…”
Section: Introductionmentioning
confidence: 97%
“… 6 - 9 Recent animal studies have also linked gestational phthalate exposures to altered heart development and function. 10 - 12 Likewise, human studies demonstrate an association between both pediatric and adult phthalate exposure and adverse cardiovascular outcomes. 13 - 16 However, few studies in humans have investigated the effects of perinatal exposures on cardiovascular health.…”
Section: Introductionmentioning
confidence: 99%